Evaluation Of Laparoscopic Versus Open Appendectomy In Terms Of Recovery Time, Complications, And Hospital Stay: A Cross-Sectional Study - Naganagoudar, Harshagouda; Kumar K H, Praveen; R Navalyal, Sanjeev; Hoogar, Prafullachandra (Journal of Neonatal Surgery, 2025)
Background: Appendicitis is one of the most common surgical emergencies worldwide. While open appendectomy (OA) has been the gold standard treatment for over a century, laparoscopic appendectomy (LA) has gained popularity in recent decades. This study aimed to evaluate and compare the outcomes of laparoscopic versus open appendectomy in terms of recovery time, postoperative complications, and duration of hospital stay. Methods: A cross-sectional study was conducted at the Department of General Surgery, KAHER's J.G.M. Medical College, Hubballi, from January 2023 to December 2023. A total of 120 patients diagnosed with acute appendicitis were included in the study. Patients were divided into two groups: 60 patients underwent laparoscopic appendectomy (LA group) and 60 underwent open appendectomy (OA group). Demographic data, operative time, postoperative pain scores, analgesic requirements, time to oral intake, complications, length of hospital stay, and time to return to normal activities were recorded and analyzed. Statistical analysis was performed using SPSS version 25.0. Results: Both groups were comparable in terms of demographic characteristics and severity of appendicitis. The mean operative time was significantly longer in the LA group (58.35 ± 12.42 minutes) compared to the OA group (42.18 ± 9.75 minutes) (p<0.001). However, the LA group demonstrated significantly reduced postoperative pain scores (Visual Analog Scale scores of 3.2 ± 1.1 vs. 5.4 ± 1.3, p<0.001), lower analgesic requirements (1.2 ± 0.5 vs. 2.3 ± 0.7 doses, p<0.001), shorter time to oral intake (14.6 ± 4.3 vs. 21.8 ± 6.2 hours, p<0.001), reduced wound infection rates (3.3% vs. 15%, p=0.026), shorter hospital stay (2.1 ± 0.8 vs. 4.2 ± 1.4 days, p<0.001), and earlier return to normal activities (12.3 ± 3.2 vs. 18.7 ± 4.6 days, p<0.001). Conclusion: Despite longer operative times, laparoscopic appendectomy offers significant advantages over open appendectomy in terms of reduced postoperative pain, lower analgesic requirements, decreased wound infection rates, shorter hospital stay, and quicker return to normal activities. These findings support the use of laparoscopic appendectomy as the preferred approach for the management of acute appendicitis